Chapter Maverick: Experimentally Testing a Conjecture of the Antitrust Authorities - Engel, Christoph (De Gruyter, 2020)
The book identifies conditions for trust and cooperation. It highlights unintended consequences of individually rational behavior, and shows how trust and cooperation change dependent on social embeddedness. Such analyses inspire experimental tests in lab conditions, but also tests through empirical applications in field studies. The results of this mixed-method approach can in turn be used to inspire further theoretical work.